Electrospun Bioactive Fibers of Pcl/Starch Loaded with Bioglass Nanoparticles with Potential Application in Bone Tissue Engineering: An in Vitro and in Vivo Study - Saavedra-Gonzalez, M (Editions de Sante, 2025)
Regenerating damaged bone tissue is a clinical challenge that can be tackled through bone tissue engineering using biopolymers and bioactive particles. This study developed bioactive electrospun fibers by incorporating 5 wt% bioglass nanoparticles (BG) into a polycaprolactone (PCL) and starch solution. The morphology, water retention, degradation, thermal and mechanical properties, and in vitro bioactivity of the fibers were examined. The fibers had diameters ranging from 311 to 438 nm. The PCL/Starch/BG scaffolds showed a 1700 % increase in water absorption after 24 h and a 37 % degradation rate, higher than neat PCL. Thermal analysis revealed that starch increased crystallinity by 9 %, while BG reduced it by 7 %, resulting in intermediate crystallinity in the composite scaffold. The incorporation of starch, BG, or both into the PCL scaffolds reduced Young s modulus and tensile strength but increased the elongation at break compared to pure PCL. After 14 days, SEM-EDS, FT-IR, and XRD analyses indicated a biomineralization increase in PCL/Starch/BG scaffolds, confirming the synergistic effect of starch and bioglass nanoparticles in enhancing bioactivity. The scaffolds promoted the cell adhesion and viability of MG-63 osteoblast-like cells. In vivo , the scaffolds showed superior biocompatibility and bioresorbability after 60 days of subdermal implantation in Wistar rats. These bioactive, biocompatible, and bioresorbable PCL/Starch/BG scaffolds show promise for bone tissue engineering applications. © 2025 Elsevier B.V.